Implementation of a Program to Tackle Dental Caries in Schoolchildren in the State of São Paulo through Continuing Education - Amanda Iida Giraldes; Luana Camila Brisolla Ferreira; Ana Maria Cervato-Mancuso; Fernanda Campos de Almeida Carrer (O Mundo da Saúde)
Despite the advances of the National Oral Health Policy (Brasil Sorridente Program) in reducing the prevalence of caries, challenges persist, especially among more vulnerable groups. This study aimed to describe and analyze the process of the first seven months of implementing a government program of Continuing Education to tackle dental caries in schoolchildren in the state of São Paulo, using Information and Communication Technologies (ICTs) to disseminate Minimal Intervention Dentistry practices in partnership with the University. This is a case report with a qualitative-quantitative approach. Data sources included document analysis and statistics produced by YouTube. Classes were conducted via the YouTube platform, with interaction through WhatsApp groups and Google Classroom. Workshops were developed to support the implementation process of the new oral health care model in the state. The experience reported in this study highlights the effectiveness of using ICTs, as a considerable audience was reached, with at least one representative from each Regional Health Department (DRS) present. There was a higher prevalence of access via mobile devices, underscoring the potential of technologies to complement traditional strategies and help reduce inequalities in access. Collaboration between teaching, service, and the community allowed for implementation aligned with the specificities of each municipality, highlighting the role of science in professional practice. Furthermore, it is noteworthy that Continuing Education empowered workers, as information from professionals who participated in virtual clinics was disseminated to service professionals.